DIGITALISASI PEMASARAN: PENDAMPINGAN STRATEGIS UNTUK MENDORONG KETAHANAN UMKM DI ERA DIGITAL DI LENGKONG KARYA, SERPONG UTARA - Tantri, Sakina Nusarifa; Riyani, Etik Ipda; Hardiana, Nadhira (Gandhi: Jurnal Pengabdian Kepada Masyarakat, 2025)
With the increasing number of MSMEs, strong business resilience is needed to face increasingly tight business competition. The large potential of MSMEs in Lengkong Karya Village, North Serpong District, South Tangerang City, Banten Province, can increase opportunities for expanding marketing reach. However, this is not balanced with the ability of MSME actors to strive for marketing following market developments and tastes. This results in MSMEs not developing optimally. Therefore, the PkM team conducted training and mentoring in digital marketing for MSMEs in Lengkong Karya. This mentoring aims to help MSMEs to accelerate growth and increase the resilience of MSME businesses. A total of 25 MSME actors attended this training and mentoring. This series of training and mentoring activities is carried out in 3 (three) stages, namely the need assessment stage, training and mentoring (provision of digital marketing materials and mentoring synchronously and asynchronously), and monitoring and evaluation (to measure the effectiveness of training and mentoring. These three stages are carried out to ensure that the implementation of the PkM program can provide measurable results and real impacts. The results of this mentoring are that MSME actors experience increased knowledge, skills, experience, and attitudes in marketing their products digitally. Thus, this PkM program can increase the resilience of MSME businesses in Lengkong Karya, North Serpong, South Tangerang. Keywords: digital marketing, training, assistance, MSMEs, business resilience